'You are here': locating 'spirituality' on the map of the current medical world. Issue 5 (September 2015) - Ramakrishnan, Parameshwaran
Abstract : Purpose of review: Clinical works at the intersection of 'spirituality, religion, theology and medicine' are studied to identify various aspects of what constitutes spirituality, what contributes to spiritual health and how to provide spiritual-healers for our current health-care system. Recent findings: Spiritual care in the current medical world can be classed grossly into two departments: complementary and alternative medicine, considered as proxy variable for spirituality, and physician-initiated clinical Chaplaincy, informed by theology. The large body of research on 'self' as a therapeutic tool, though, falls into subtle categories: phenomenological studies, empathy, embodied care, and mindfulness-based therapies. Development in the field of 'spiritual medicine' has focused on spirituality-related curricula. Summary: As mindfulness-based meditation programs help build deep listening skills needed to stay aware of the 'self', Clinical Pastoral Education trains the chaplain to transcend the 'self' to provide embodied care. Clinical chaplaincy is the destination for health-care professionals as well as theological/religious scholars who have patients' spiritual health as their primary focus. Medical education curricula that train students in chaplain's model of transpersonal-mindfulness/empathy founded on neuro-physiological principles would help them gain skills in embodied care. Such education would seamlessly integrate evidence-based clinical practice and spiritual-theological concepts.